Risk assessment and management in Malaysian teacher training programmes - Syed Abdullah, Sharifah Intan Sharina; Mohamad Nasri, Nurfaradilla; Mohd Ayub, Ahmad Fauzi (Human Resource Management Academic Research Society, 2018)
Critical review of literature revealed that, risk assessment and management in educational field is commonly discussed in the literature of outdoor education. This is because being surrounded with higher risks is one of the natures of its implementation and features that distinguished outdoor education from indoor learning. Nonetheless, safety issues during the learning process, particularly, in other subjects have received relatively less attention. This paper aims to examine other learning conditions that may involve risks or safety issues that is relevant in the teaching and learning of all subjects regardless whether the learning takes place outdoor or indoor. In this paper, we suggest that risk may occur everywhere, indoor and outdoor, and risk assessment and management should be carried out by all educators regardless the approach and the venue of learning. Following this suggestion, further implication of this paper is a suggestion to develop new curriculum on risk assessment and management for all fields in teacher training programmes.